The Development Tendencies of the Institutional Transformation of Family and Mahalla Structures Within the Framework of Ongoing Socio-Legal Reforms in the Republic of Uzbekistan - Yuldosheva Shokhista Tolqinovna (Indonesian Journal Publisher, 2026)
This scholarly article presents an in-depth analysis of the institutional transformation of family and mahalla (community) structures within the framework of ongoing socio-legal reforms in the Republic of Uzbekistan. It explores their practical functions grounded in legal norms, as well as their envolving role in the contemporary sociopolitical landscape. The study highlights the mediating role of these institutions in the local implementation of state policies, their contribution to the consolidation of social stability, and their influence on the formation of civil society. Furthermore, a comparative examination with international practices identifies prospective pathways for the sustainable development of these community-based institutions.